Strong Promoting Effect of Gold Nanoparticles on the CO Abatement Catalytic Activity of CoOx/Clay‐Bonded SiC Catalysts Produced by AA‐MOCVD Method Using Co(acac)2 as Precursor. Issue 44 (23rd November 2020) - MirMoghtadaei, Golnoosh; Ghosalya, Manoj K.; Artiglia, Luca; van Bokhoven, Jeroen A.; Falamaki, Cavus
Abstract: Clay‐bonded SiC supported cobalt oxide catalysts were produced by the aerosol‐assisted metal organic chemical vapor deposition method (AA‐MOCVD) using Co(acac)2 as precursor. Deposition temperatures 270 and 300 °C were the most appropriate for the synthesis of a composite catalyst of high activity for the CO conversion reaction. A cone‐shaped crystal habit is the dominant morphology. The catalysts were decorated with Au nanoparticles (NPs) of sizes in the range of 5–10 nm. This substantially improved the activity of the catalysts, lowering the onset temperature of activity by about 50 °C. Ambient‐pressure X‐ray photoelectron spectroscopy (APXPS) was used to investigate in situ the electronic state of cobalt and gold during CO oxidation. APXPS results show that while Au remains in the metallic state during the reaction, it enhances the reduction of Co 3+ to Co 2+ . Au NPs adsorb CO molecules from the gas phase and supply them to the neighbor cobalt oxide particles. Abstract : CoOx /clay‐bonded SiC catalysts produced by aerosol assisted‐ metal organic chemical vapor deposition (AA‐MOCVD) method are active in the CO oxidation reaction. The T270, T300 and T330 samples refer to a deposition temperature of 270, 300, and 330 °C, respectively. Co(acac)2 has been used as precursor. However, when decorated with Au nanoparticles, the reaction rate is greatly enhanced. In situ ambient‐pressure X‐ray photoelectron spectroscopy (APXPS) analysis showed that Au nanoparticles promote Co 3+ into Co 2+ reduction reaction, without changing their metallic character.